A Prospective, Comparative Evaluation on Totally Implantable Venous Access Devices by External Jugular Vein versus Cephalic Vein Cutdown. Issue 6 (June 2018) - Iorio, Olga; Gazzanelli, Sergio; D'ermo, Giuseppe; Pezzolla, Angela; Gurrado, Angela; Testini, Mario; Toma, Giorgio De; Cavallaro, Giuseppe
The request for totally implantable venous access devices (TIVADs) has rapidly grown up through the last decades. TIVADs are implanted by direct vein puncture or by surgical approach with vein cutdown. The authors present a comparative prospective study evaluating external jugular vein (EJV) and cephalic vein cutdown techniques. Two hundred and fifteen patients were consecutively submitted to TIVAD implantation to perform chemotherapy. Patients were divided in two groups, depending on the implantation technique. Group A patients (106) underwent implantation via EJV cutdown and group B (109) patients underwent implantation by cephalic vein cut-down. The following variables were investigated: operating time, need for conversion to other approaches, complications, and intraoperative and postoperative pain. In Group A patients, the success rate of the procedure was 100 per cent, whereas in 11 patients (10.1%) of Group B, a modification of the initial approach was needed. Mean operative time was 23.9 ± 9.2 minutes in Group A and 35.4 ± 11.9 in Group B, and this was statistically significant (P < 0.05). Complication rates at 30 days were similar. Considering intraoperative pain, a difference was found between the two groups because the mean value of pain in Group Awas lower than that in Group B (4.13 ± 0.3 vs 5.22 ± 1.24), even if not significant. External jugular vein cutdown approach is quick and safe and allows a very high success rate with very low risk of complications. For these reasons, this approach could be considered as a first choice in TIVAD placement.